Improvements in addressing climate factors in urban planning and design - Ebrahimabadi, Saeed (Luleå tekniska universitet, Arkitektur och vatten, 2012)
Urban settlements located in subarctic regions have particular characteristics due to their climate. Climate and weather conditions influence people’s attendance in public spaces, their travel habits and recreational activities. In the subarctic regions, this influence is more visible due to greater seasonal differences. Urban design that deals with the generation and change of urban form can influence the impact of climate factors. Such interventions can be especially influential in the subarctic regions.This thesis focuses on addressing climate factors in urban design and transportation in the subarctic regions of Sweden. On one hand, it focuses on problems of incorporating climate factors into urban design, and on the other hand, it investigates travel patterns in relation to subarctic climate. The problems of urban design in subarctic regions were investigated by conducting a literature review and interviews with the planners from some of the Swedish northern municipalities. To study travel patterns in relation to cold climate, two travel surveys were conducted in Kiruna, a town located in the Northern Sweden. These issues are analysed and discussed in a covering essay and three attached papers. The interviews with planners show that climate considerations have a low impact on urban planning practices in these regions. The absence of a positive attitude towards cold climate, lack of knowledge and analytical techniques to be used in design, and weak relation between knowledge of climate factors and urban design practice are some of the major problems. Further, the interviews highlighted that dealing with snow in urban spaces (snow removal, better use of snow) is a crucial issue for these municipalities. The travel surveys in Kiruna demonstrated that car trips made a large proportion of all trips made in Kiruna while a very small part of trips were made by bicycle and public transport. The proportions of trips made by different transport modes (modal share) did not vary significantly in accordance to seasonal ...